RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN PENGAJUAN BANTUAN DAN PENYULUHAN KELOMPOK TANI BERBASIS WEB (STUDI KASUS : DINAS KETAHANAN PANGAN DAN PERTANIAN KABUPATEN JEPARA) (Science and Technology (SciTech), 2023)
Farmers Group is an association of farmers consisting of administrators and members that has the aim of increasing agricultural yields as well as the standard of living of farmers, especially in their respective farmer groups. Farmer groups are used as a medium for organizational learning and cooperation among farmers. The problem that often occurs at this time in farmer groups, especially farmer groups in Jepara Regency, is regarding transparency in the management of funds or assistance and distribution to farmer group members. These problems cause ineffectiveness in carrying out each activity. To overcome this, it is important to set a schedule so that the activities to be carried out run smoothly. Based on the existing problems, a web-based farmer group management information system for the case study of the Food Security and Agriculture Office of Jepara Regency was built. The system is expected to be able to assist employees of the Jepara Regency Food Security and Agriculture Office in designing and building a farmer group management system, especially in the field of extension and POKTAN assistance.